The Role of Early Childhood Education Teachers in Communicating and Managing Schools Safe - Afrianti, Nurul; Arif Hakim; Erhamwilda; Masnipal; Ayi Sobarna; Via Eka Lestari (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
When a disaster occurs, students are the most vulnerable to the effects, especially if the disaster occurs while the children are at school. With the large number of potential disasters that occur, disaster education is very important to do early on, and this is done by equipping early childhood teachers about disaster education and managing disaster-safe schools. In the end, education and management of disaster-safe schools can be conveyed to children through play activities according to the principles of learning for early childhood. Efforts to provide disaster education from an early age is an important and fundamental action that is not only an act of curriculum development or enrichment alone, but is also a preventive action for the life of every child in dealing with this phenomenon in the future, so that when faced with real events every child has optimal readiness to deal with it.